Bacillus “next generation” diagnostics: moving from detection toward subtyping and risk-related strain profiling - Ehling-Schulz, Monika; Messelhaeusser, Ute (Frontiers in Microbiology, 2013)
The highly heterogeneous genus Bacillus comprises the largest species group of endospore forming bacteria. Because of their ubiquitous nature, Bacillus spores can enter food production at several stages resulting in significant economic losses and posing a potential risk to consumers due the capacity of certain Bacillus strains for toxin production. In the past, food microbiological diagnostics was focused on the determination of species using conventional culture based methods, which are still widely used. However, due to the extreme intraspecies diversity found in the genus Bacillus, DNA based identification and typing methods are gaining increasing importance in routine diagnostics. Several studies showed that certain characteristics are rather strain dependent than species specific. Therefore, the challenge for current and future Bacillus diagnostics is not only the efficient and accurate identification on species level but also the development of rapid methods to identify strains with specific characteristics (such as stress resistance or spoilage potential), trace contamination sources, and last but not least discriminate potential hazardous strains from non-toxic strains.